Oscillatory Asymptotics for the Airy Kernel Determinant on Two Intervals. (26th August 2020) - Blackstone, Elliot; Charlier, Christophe; Lenells, Jonatan
Abstract: We obtain asymptotics for the Airy kernel Fredholm determinant on two intervals. We give explicit formulas for all the terms up to and including the oscillations of order 1, which are expressed in terms of Jacobi θ -functions.